ANALISIS PERAN AKTOR DALAM FORMULASI KEBIJAKAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERKOTAAN DI KELURAHAN KEMIJEN, KOTA SEMARANG - Husnul Yakin; Susi Sulandari; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
The implementation of PNPM-MP is still have lots of weakness, it is proven that the number of poor families target years 2009-2011 and 2011-2013 Kemijen Village Semarang are still same. Based on the observation by researcher, PNPM-MP resistance due to weak human resources; institutional coordination; differences in perceptions and lack of understanding of the guidelines. Based on the description of the background of the problem, can be taken 3 problem, they are: How the role of actors in policy formulation for PNPM-MP on Kemijen Village Semarang City?; What are the obstacles in the implementation of PNPM-MP? And how handling the weakness in the implementation of PNPM-MP? According to James Anderson Charles Lindblom and James P. Lester and Joseph Stewart, Jr. actors or actors participate in policy formation process can be divided into two groups, namely the cast and the cast as well as official and unofficial. Which belongs to the actor and is the official government agency (bureaucracy), the president (executive), legislative and judicial. While belonging to the unofficial role include interest groups, political parties and individual citizens. This research uses the theory of James E. Anderson, the policy is as the behavior of a number of actors (officials, groups, government agencies) or a set of actors in a particular policy area. Talk of the policy cannot get out of the relationship between interest groups, both at the government and society at large. According to Walter J.M. Kickert, Erik-Hans Klijn and Joop F.M. Koppenjan, actors cannot be separated from each other and have connection with each other. According to Sri Suwitri, strong policy networks are the five things they are the interests of network members, membership, interdependence, isolation from other networks, and the distribution of resources among the members. Network integration of high membership, membership has stability, interdependence network members, and isolation from other networks. The larger the policy network will strengthen the pluralistic society. This study uses qualitative research and data collection based on interviews with key informants and direct observation conducted by researchers at Kemijen Village Semarang City.Based on theory, the actor cannot move on their own without collaboration of other actors, so that is needed a network diagram to known the role of each actor. In the implementation of PNPM-MP should refer to the operational guidelines PNPM-MP and develop accessibility advisory assistance from the sub-district or districts. Then, it is necessary establishes public complaints unit to accommodate all the complaints that can be sought alternative solutions. In finding such alternative PNPM-MP need to use incremental models so that any problems that arise can be done rectification and correction to create anew policy. Suggestions in this study are it need a similar view from actors to improve the welfare ofsociety and transparency in the implementation of PNPM-MP.